Voter Equalization and Turnout Bias After Electoral Reform: Evidence from Chile's Voluntary Voting Law. (November 2019) - Brieba, Daniel; Bunker, Kenneth
ABSTRACT: It has normally been argued that because compulsory voting systems present higher turnout rates relative to voluntary voting systems, they do not generate as many biases between different groups of voters. This article qualifies that view. It argues that in cases in which compulsory voting does not ensure near-universal participation, there is no certainty that switching to voluntary voting will increase inequalities. This issue is examined by looking at Chile, a democracy that moved from compulsory voting to voluntary voting in 2012. The research finds that while the reform generated class bias in urban districts, it also substantially reduced age bias and, in national elections, equalized participation between small and large districts. The conclusion is that abandoning compulsory voting does not necessarily increase turnout biases, since much depends on the structure of preexisting biases and how these are conditioned by particular electoral institutions.